The issues of oppressed groups’ access to collectively managed resources: an empirical analysis - Dhakal, Bhubaneswor (Banko Janakari, 2007)
Oppressed groups’ problem in collective management of resource is examined in the case of Kami’s (Blacksmith) access to charcoal in community forests in Nepal. A field survey shows that almost a half forest user groups have excluded the Kami for charcoal collection. In the government policies, rights of households with special needs are not clearly defined and protected. In an econometric analysis of the user groups, this study identified forest size, group size, intensive external support and groups’ meeting frequency are the factors determining the charcoal distribution in community forests. Key words: Community forest, exclusion, livelihood, protected rights, special need group Banko Janakari Vol.16(1) 2006 pp25-31